Social Media Marketing Role in Building Brand Awareness and Purchase Intention among Generation Z - Imas Chandra Pratiwi; Yanita Ella Nilla Chandra; Kathrine; Erlyn Rosalina; Titik Purwinarti; Risya Zahrotul Firdaus (University of Merdeka Malang, 2025)
The expansion of digital marketing has prompted innovative marketing strategies among hand and body lotion brands, including Marina as one of the most popular hand and body lotion brands in Indonesia. This study aimed to examine the impact of user-generated content and influencer on the purchase intention of Marina hand and body lotion, both directly and indirectly, through brand awareness among Generation Z in Jakarta. A quantitative study was conducted with 410 participants through purposive sampling. Overall, 5 out of 6 hypotheses were statistically accepted. Influencer was found to have an insignificant effect on the purchase intention of Marina among Gen Z directly. The statistical results indicate that brand awareness serves as a crucial mediating variable between user-generated content and influencer toward purchase intention. The findings indicate that marketing strategies aimed at Gen Z should focus on enhancing user engagement and promoting authentic brand storytelling to increase brand awareness and translate it into purchase intention. This study also presents several suggestions for future research.